Znaczenie Egiptu w apokaliptyce – Λόγος Τέλειος /Asclepius (NHC VI, 8: 70,3-76,1; Ascl. 24-27) - Agata Sowińska (Vox Patrum, 2012)
The aim of this paper was to present the Egyptian land in two apocalyptic texts both written in a Coptic language. First – the Apocalypse of Elijah (written in two Coptic dialectical versions: Sahidic and Achmimic) – shows a typical biblical meaning of Egypt as a place full of pain, death and fear. On the other hand, in the Codex VI of the Nag Hammadi Library there is the Apocalypse which gives us quite different image of that part of African land. This very Apocalypse is called the Apocalypse of Hermes Trismegistos or the Hermetic Apocalypse (written in Sahidic dialect and partly in the ancient Greek, whole test is composed in a Latin version and attributed to Ps-Apuleius of Madaura). Here, Egypt seems to be a paradise – image of heaven, land of gods and beautiful temples. But suddenly, that peaceful part of the world turns into “hell” with death, blood and pain – just like in the Apocalypse of Elijah. Our purpose was to analyze those two Coptic Apocalypse, compare the results and finally, try to find the answer on the basic questions: Egypt – heaven or hell? Could it be that this land was full of blood because of monotheistic religion?